POTENSI EKSTRAK BUNGA TELANG (CLITORIA TERNATEA) SEBAGAI PEWARNA ALAMI LOKAL PADA BERBAGAI INDUSTRI PANGAN: (The Potential of Extract Butterfly Pea Flower (Clitoria ternatea L.) as a Local Natural Dye for Various Food Industry) - Lisa Angriani (jurnal1, 2019)
Butterfly pea flower is a plant containing anthocyanin pigment which has the potential to be developed as a local natural dye in various food industry. Local natural dyes in various industries besides enhancing color quality attributes can also provide antioxidant, anticancer, and anti-inflammatory effects. Butterfly pea flower extract has good stability in acidic conditions. The purpose of this study was to identify the potential of butterfly pea flower extract as a local natural dye for the food industry, this study focused on variations in pH 2-10 and storage temperatures. The results showed that at pH 4-5 anthocyanin Butterfly pea flower had concentrated blue-purple color and very good stability and were able to survive for 2 months did not appear to decrease at room temperature. Butterfly pea flower extract at pH 6-7 has a color that fades after being stored for several days, but can last up to 6 months at refrigerator temperature storage. Butterfly pea flower extract can be used as a local natural dye in the manufacture of ice cream, syrup, coockies, bread and various other types of food products.